79.2k views
3 votes
Can you please help me with this equation. I will send a screenshot with the problem I am having difficulty with.

Can you please help me with this equation. I will send a screenshot with the problem-example-1
User Conti
by
5.0k points

1 Answer

3 votes

Step-by-step explanation

Given


48(2)/(9)+(-39(8)/(9))

We will have;


\begin{gathered} 48(2)/(9)+(-39(8)/(9)) \\ convert\text{ mixed numbers to improper fractions} \\ =(434)/(9)+\left(-(359)/(9)\right) \\ =(434)/(9)-(359)/(9) \\ \mathrm{Apply\:the\:fraction\:rule}:\quad (a)/(c)-(b)/(c)=(a-b)/(c) \\ =(434-359)/(9) \\ \mathrm{Subtract\:the\:numbers:}\:434-359=75 \\ =(75)/(9) \\ Reduce\text{ to lowest fraction} \\ =(25)/(3) \end{gathered}

The solution derived has a positive sign. Therefore;

Answer: Option A

User Muahmmad Tayyib
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.